2022
DOI: 10.3389/fonc.2022.864647
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer With Peritoneal Metastasis—A Comprehensive Review of Current Intraperitoneal Treatment Modalities

Abstract: The treatment of patients with peritoneal metastasis from gastric cancer continues to evolve. With various forms of intraperitoneal drug delivery available, it is now possible to reach the sites of peritoneal metastases, which were otherwise sub-optimally covered by systemic chemotherapy, owing to the blood peritoneal barrier. We conducted a narrative review based on an extensive literature research, highlighting the current available intraperitoneal treatment options, which resulted in improved survival in we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 90 publications
0
13
0
3
Order By: Relevance
“…In the presence of PC, whenever the patient is deemed resectable and presents a peritoneal cancer index not greater than 6, we advise for standard neoadjuvant chemotherapy, which may be supplemented by 2 concomitant PIPAC to optimize resectability and cure rate. Indeed, PIPAC performed in the context of unresectable GC achieved a pathologic response in more than 60% and allowed conversion to resectability in up to 14% of the patients [ 61 , 63 , 72 , 73 ]. The addition of PIPAC to systemic neoadjuvant chemotherapy further allows for a dynamic laparoscopic response evaluation, including iterative biopsies and tumor regression grading to inform oncologic treatment and resectability of the primary cancer and PC.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of PC, whenever the patient is deemed resectable and presents a peritoneal cancer index not greater than 6, we advise for standard neoadjuvant chemotherapy, which may be supplemented by 2 concomitant PIPAC to optimize resectability and cure rate. Indeed, PIPAC performed in the context of unresectable GC achieved a pathologic response in more than 60% and allowed conversion to resectability in up to 14% of the patients [ 61 , 63 , 72 , 73 ]. The addition of PIPAC to systemic neoadjuvant chemotherapy further allows for a dynamic laparoscopic response evaluation, including iterative biopsies and tumor regression grading to inform oncologic treatment and resectability of the primary cancer and PC.…”
Section: Resultsmentioning
confidence: 99%
“…With the continuous exploration of HIPEC and improvement of its instruments, the application of HIPEC in gastrointestinal tumors has been quite mature ( 23 ). In recent years, a number of studies have suggested that HIPEC does not increase the incidence of postoperative complications ( 24 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer ranks as the third leading cause of cancer-related mortality globally despite being the sixth most prevalent malignancy 1 , 2 . Among the various forms of advanced gastric cancer, peritoneal metastases (PM) represent the most formidable threat to patient survival, with a dismal prognosis 3 5 . Even following curative surgery, nearly half of patients with advanced gastric cancer displaying serosal involvement (T4) experience peritoneal recurrences 6 8 .…”
Section: Introductionmentioning
confidence: 99%